Perancangan Mine Sequence untuk Mendukung Target Produksi Bulan April pada Tambang Nikel Laterit Pit Hill16 PT Hillconjaya Sakti - Irga loti Rante; I Putu Putrawiyanta; Noveriady Noveriady; Nuansa Mare Apui Ganang; Yunida Iashania (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study is motivated by the discrepancy between production targets and actual field performance caused by dynamic operational conditions, such as equipment productivity and effective working time. The objective of this research is to redesign the production target and develop a more realistic mine sequence using a rolling plan approach at Pit Hill16. The method includes analyzing the productivity of loading and hauling equipment based on cycle time data, calculating effective working time, and determining production targets using the rolling plan method. Furthermore, mine sequence design is developed based on the adjusted production targets. The results indicate that the productivity of loading equipment is 241.98 BCM/hour for the EC480DL excavator and 123.27 BCM/hour for the EC210DL excavator, while hauling equipment productivity is 40.24 BCM/hour. The April production target based on the rolling plan is 275,913 BCM, which can be achieved through mine sequence design with a volume of 277,839 BCM, resulting in a difference of +1,926 BCM, still within acceptable planning tolerance. Therefore, the rolling plan approach is proven to produce a more adaptive and realistic mining plan under actual field conditions.